2021
DOI: 10.3390/app11199212
|View full text |Cite
|
Sign up to set email alerts
|

Sport Performance Analysis with a Focus on Racket Sports: A Review

Abstract: Athletes, both professional and amateur, are always looking for ways to improve their performance. With the introduction and increasing availability of modern technologies and smart devices arose the need to measure and analyze performance, but likewise, the use of these innovations as a competitive advantage also arose. Scientific publications reflect the wide range of available approaches and technologies, as well as the growing interest in various sports. As a result, we concentrated on a systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 166 publications
0
2
0
Order By: Relevance
“…After analyzing the results, it was found that the tested competitor scored the most points directly from service (10) and return (10), in actions after his service (servicecounterattack: 10), and from counterattack actions after his return (11). The obtained results also show the great use of the forehand serve in winning actions (directly and in the first stroke after his service) and in the forehand push, both as a return (5) and in the exchange in play immediately after the return (7).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…After analyzing the results, it was found that the tested competitor scored the most points directly from service (10) and return (10), in actions after his service (servicecounterattack: 10), and from counterattack actions after his return (11). The obtained results also show the great use of the forehand serve in winning actions (directly and in the first stroke after his service) and in the forehand push, both as a return (5) and in the exchange in play immediately after the return (7).…”
Section: Resultsmentioning
confidence: 84%
“…The observation and analysis of the game or the player's behavior and actions are very important aspects of optimizing sports training in table tennis. Performance analysis is an important part of an athlete's development and coaching process, and it is a significant competitive advantage [5]. Notational analysis, the purpose of which is to obtain objective data from the course of the game or the actions of the player (team), allows one to gain knowledge about the tactics used, techniques used, and activity in various periods of sports competition [6].…”
Section: Introductionmentioning
confidence: 99%
“…Racket sports are a subset of ball games and may also be classified as those games where tools, such as rackets, are used to propel or strike a ball [1,2]. These matches typically involve two to four players and are centered around the objective of striking the ball so that the opponent cannot return it [3,4]. Racket sports fall into two main categories: net sports, played on designated courts like tennis, badminton, and table tennis, and non-net sports, played on shared courts, such as squash [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, during vigorous exercise, the body relies on the ATP-CP system, emphasizing the importance of explosive power [3,10]. However, as the activity continues, the rapid depletion of ATP and CP stores due to their limited capacity prompts a transition to the lactate system when these reserves prove inadequate for sustained physical exertion [4,11]. In racquet sports, the body perpetually shifts between energy systems as the intensity and duration of play evolve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation